Enhanced Beacon Scheduling for Cluster Tree Topology in Wireless Personal Area Network - Dyg Khayrunsalihaty Bariyyah, Bt Abang Othman (Universiti Malaysia Sarawak (UNIMAS), 2019)
IEEE 802.15.4 Low Rate Wireless Personal Area Network (LR-WPAN) is one of the standards for Wireless Sensor Network (WSN) which provides low power multihop transmission in Wireless Personal Area Network (WPAN). The LR-WPAN has two types of nodes which can either be full function devices (FFD) or reduced function devices (RFD). The number of FFD and RFD in a WPAN determines the two types of topology for the network: star and peer-to-peer. Star topology restricts communication between a PAN-C and RFD, while peer-to-peer topology may establish a mesh or tree topology depending on the nodes’ restrictions. A cluster tree topology extends network with less FFD and as a result, reduces routing complexity. The coordinators in a cluster tree topology network transmit beacons periodically to allow nodes synchronization and communications. However, if concurrent beacons transmission is within the same transmission range, it will cause beacons collision, therefore resulting in poor network performance. In order to increase network performance, an enhancement on the available beacon scheduling method, superframe adjustment and beacon transmission scheme (SABTS) was introduced. This enhanced method is called coordinator clustering SABTS (CC-SABTS). CC-SABTS improves the gap in SABTS which causes delay in beacon transmission and communication by clustering coordinator nodes that are separated by two length radius to avoid an overlapping transmission range. The non-overlapping coordinators can be clustered to share beacon transmission time and this reduces delay for beacons transmission. Hence, nodes can start their communications process earlier. This study compares the average throughput, packet delivery ratio (PDR), end to end delay and packet loss between SABTS and CC-SABTS. Simulation results showed that in a network with varied interarrival rate (INTV), CC-SABTS outperformed conventional SABTS up to 39%, 5%, 22% and 29% for average throughput, PDR, end to end delay and packet loss, respectively. CC-SABTS also improved the conventional SABTS by 37%, 30%, 29% and 9% for average throughput, PDR, end to end delay and packet loss, respectively for a varied number of end devices. The average throughput, PDR, end to end delay and packet loss also improved by 3%, 25%, 8% and 22%, respectively in a varied packet size network. In addition, an improvement up to 41%, 30%, 41% and 27% for average throughput, PDR, end to end delay and packet loss was achieved in a varied density network. Lastly, the CC-SABTS worked 62% and 18% better for average throughput and PDR when simulated in a constant bit rate (CBR) traffic environment. However, in the case of average end to end delay and packet loss, CC-SABTS improved performance up to 30% and 69%, respectively in Poisson traffic environment. In conclusion, the CC-SABTS improves network significantly compared to the conventional SABTS when simulated in a varied interaarival rate, end devices, packet size, network density and network traffic.